2021
DOI: 10.3390/app11093790
|View full text |Cite
|
Sign up to set email alerts
|

Separation of Zr from Zr-2.5Nb by Electrorefining in LiCl-KCl for Volumetric Decontamination of CANDU Pressure Tube

Abstract: This study presents an experimental investigation on Zr separation from Zr-2.5Nb by anode potentiostatic electrorefining in LiCl-KCl-ZrCl4 0.5 wt. % at 773 K for irradiated CANDU pressure tube decontamination. By the ORIGEN-2 code calculation, radioactive characteristics were investigated to show that Nb-94 was the most significant radionuclide with an aspect of waste level reduction by electrorefining. Three electrorefining tests were performed by fixing the applied potential as −0.9 V (vs. Ag/AgCl 1 wt. %) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Some studies reported that pure Zr metal could be electrochemically deposited on inert electrodes by a constant-potential method. [18][19][20] However, the adhesion strength of deposits in their studies was also poor. Thus, detached precipitates in the molten salt should be collected by the catch crucible or the desalting process.…”
mentioning
confidence: 94%
See 2 more Smart Citations
“…Some studies reported that pure Zr metal could be electrochemically deposited on inert electrodes by a constant-potential method. [18][19][20] However, the adhesion strength of deposits in their studies was also poor. Thus, detached precipitates in the molten salt should be collected by the catch crucible or the desalting process.…”
mentioning
confidence: 94%
“…14 Accordingly, the electrodeposition and redox behavior of Zr in molten LiCl-KCl salt has been actively studied to develop a suitable process. [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] Until recently, there has been considerable progress in understanding the redox behavior of Zr in molten LiCl-KCl salt. On the other hand, the electrodeposition of Zr metal in molten LiCl-KCl salt is still a challenge since because of the co-deposition of insoluble zirconium monochloride (ZrCl) and the loss of deposits during retrieval from the molten salts.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…One promising methodology for recycling spent fuel Zralloy cladding is an electrometallurgical process that uses molten LiCl-KCl salt as a medium. [7][8][9][10][11][12][13][14][15][16][17][18][19] For such a process, the direct anodic dissolution of Zr-alloy cladding is the most straightforward strategy for administering Zr reactants into molten LiCl-KCl salts. 8,16 Since Zr-alloy cladding is generally composed of 97% or more of Zr; 8 it is essential to rigorously understand the anodic dissolution behavior of Zr in molten LiCl-KCl salt.…”
Section: Introductionmentioning
confidence: 99%
“…7–19 For such a process, the direct anodic dissolution of Zr-alloy cladding is the most straightforward strategy for administering Zr reactants into molten LiCl–KCl salts. 8,16 Since Zr-alloy cladding is generally composed of 97% or more of Zr; 8 it is essential to rigorously understand the anodic dissolution behavior of Zr in molten LiCl–KCl salt.…”
Section: Introductionmentioning
confidence: 99%